Concomitant ipsilateral femoral neck and pelvic ring fractures in the setting of a low energy fall in an elderly patient: A case report. (October 2022) - Aouad, Dany; Sakhat, Georges; Dahdouh, Raymonde; Daher, Mohammad; El Rassi, George
Abstract: Introduction: Simultaneous ipsilateral fractures of the femoral neck and pelvic ring secondary to low energy falls are an extremely rare occurrence. Consequently, there is no standardized protocol for the management of such injury. Only few other cases were reported in the literature. Case presentation: A 94-year-old woman presented with a left sub-capital femoral neck fracture, associated with comminuted and displaced fractures of the left superior and inferior pubic rami, after sustaining a fall from height. A decision was made to treat the femoral neck fracture with a left uncemented hemiarthroplasty, while the pubic rami fractures were managed conservatively. Discussion: Coexisting femoral neck and pubic rami fractures due to low energy trauma is newly emerging in literature. Consequently, an elderly patient falling from standing height might require a CT or an MRI to reach an accurate diagnosis of the resultant injuries. While hip fractures are almost always treated surgically, pelvic ring fractures are only managed invasively when the conservative approach fails. This creates a dilemma when both fractures occur simultaneously, as appropriate measures must be taken to treat the patient with lowest risk of complications. Conclusion: Low-energy fractures of the hip and pelvic ring should no longer be regarded as mutually exclusive. Any patient presenting with one of them should be investigated for the other. A consensus should be reached regarding the most appropriate technique to manage such injuries. Highlights: A fall from height may result in concurrent hip and pelvic ring fractures. If either injuries is present the other must be searched A standardized protocol on how to approach such injuries should be reached